1998
DOI: 10.2136/sssaj1998.03615995006200040033x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxalate and Soil Organic Matter on Sorption and Desorption of Phosphate onto a Spodic Horizon

Abstract: Phosphate (PO4) availability limits the productivity of pine plantations growing on Spodosols of the southeastern USA. Oxalate has been shown to interact with both the sorption and desorption PO4 onto soil mineral surfaces. In addition, organic matter, a crucial component of many soil surfaces, affects the adsorption of PO4. We studied the effects of oxalate and organic matter on PO4 sorption and desorption onto the whole soil and clay‐sized fraction of a spodic horizon from a poorly drained Spodosol of the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
2
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 7 publications
1
76
2
9
Order By: Relevance
“…Similar increases were also observed for Fe. The release of Al and Fe into solution has been attributed to the dissolution of metal oxides by organic matter (Bhatti, Comerford, and Johnston 1998;Bolan et al 1994;Fox, Comerford, and McFee 1990) and is supported by our observation of minimal release of Fe and Al for the CaCl 2 solution, which lacked DOM, and the swine effluent solution, in which minimal DOC sorption was observed. The greater release of Al in the KCl solution as compared to the CaCl 2 solution was likely due to the higher concentration of K and the fact that K has been shown to be more effective than Ca in displacing Al from soils (Chung, Zasoski, and Burau 1994).…”
Section: Phosphorus Sorption From Manuresupporting
confidence: 69%
See 1 more Smart Citation
“…Similar increases were also observed for Fe. The release of Al and Fe into solution has been attributed to the dissolution of metal oxides by organic matter (Bhatti, Comerford, and Johnston 1998;Bolan et al 1994;Fox, Comerford, and McFee 1990) and is supported by our observation of minimal release of Fe and Al for the CaCl 2 solution, which lacked DOM, and the swine effluent solution, in which minimal DOC sorption was observed. The greater release of Al in the KCl solution as compared to the CaCl 2 solution was likely due to the higher concentration of K and the fact that K has been shown to be more effective than Ca in displacing Al from soils (Chung, Zasoski, and Burau 1994).…”
Section: Phosphorus Sorption From Manuresupporting
confidence: 69%
“…For the most part, the amount of DOC sorbed to the soils was similar between the dairy and poultry extracts and with little or no DOC sorption occurring with the swine effluent (Figure 3).The large amount of sorption of DOC in the dairy manure solution may explain why DRP sorption was much lower in this solution compared to the CaCl 2 and KCl solutions. Organic matter has been shown to reduce P sorption to soils by competing with P for sorption sites as well as complexing with metal oxyhydroxides (Bhatti, Comerford, and Johnston 1998;Ohno and Crannell 1996;Ohno and Erich 1997;Singh and Jones 1976;Violante, Colombo, and Buondonno 1991). On the other hand, studies have also reported increased P sorption due to the presence of organic matter (Guppy et al 2005a;Harter 1969;Redding, Shatte, and Bell 2006; Sanyal, De Datta, and Chan 1993).…”
Section: Phosphorus Sorption From Manurementioning
confidence: 99%
“…In a recent study of German forest soils performed with P K-edge XANES spectroscopy, Prietzel et al (2016b) reported the presence of crystalline AlPO 4 in the bedrock of, e.g., BBR (24% AlPO 4 ) and MIT (35% AlPO 4 ). During pedogenesis, the adsorbed P inorg can be desorbed through displacement of other soil 30 solution anions (Bhatti et al, 1998;Violante and Pigna, 2002). The spatial pattern of P ox.inorg at BBR, CON, MIT illustrates this desorption during early and intermediate stages of pedogenesis (Fig.…”
Section: Factor Analysis 20mentioning
confidence: 99%
“…The phenomenon that adsorbed As(V) were more easily desorbed in the presence of oxalate or HA could be attributed to the reduction in sorption sites because of the effects of oxalate or HA on the soil surface characteristics (Kaiser and Guggenberger, 2003). In addition, the oxalate or HA sorbed on the subsamples could be released into the solution in the desorption process (Sibanda and Young, 1986;Bhatti et al, 1998a;Violante and Pigna, 2002) and thus would also facilitate As(V) desorption.…”
Section: Effects Of Oxalate and Ha On The Sorption Of Arsenate In Thementioning
confidence: 99%